2010
DOI: 10.1093/molehr/gaq033
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of human oocytes: association of meiotic aneuploidy and altered oocyte gene expression

Abstract: The ability to identify oocytes with the greatest potential for producing a viable embryo would be of great benefit to assisted reproductive treatments. One of the most important defects affecting oocytes is aneuploidy. Aneuploidy is also closely related with advancing maternal age, a phenomenon not well understood. This study combined a comprehensive cytogenetic investigation of 21 oocytes with a detailed assessment of their transcriptome. The first polar body was removed from all oocytes and aneuploidy asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 63 publications
5
32
0
Order By: Relevance
“…The deterioration in oocyte quality is related to a predisposition to the generation of aneuploid embryos caused by chromosomal segregation errors and abnormal spindle development, epigenetic modifications (120), and a deterioration of the oocyte cytoplasm (ooplasm), related to a decrease in mitochondria, a reduction in their quality and an increase in oxidative stress within the ooplasm (2), which can lead to promote free radical formation leading to the modification of intracellular proteins, lipids, and nucleic acids macromolecules (92) and alterations in mRNA (108). Consequently, female fertility starts to rapidly decline in a woman beyond 37 years of age, as manifest by the success rates of IVF treatment (206) and also by measures of natural fertility (192).…”
Section: Oocyte Qualitymentioning
confidence: 99%
“…The deterioration in oocyte quality is related to a predisposition to the generation of aneuploid embryos caused by chromosomal segregation errors and abnormal spindle development, epigenetic modifications (120), and a deterioration of the oocyte cytoplasm (ooplasm), related to a decrease in mitochondria, a reduction in their quality and an increase in oxidative stress within the ooplasm (2), which can lead to promote free radical formation leading to the modification of intracellular proteins, lipids, and nucleic acids macromolecules (92) and alterations in mRNA (108). Consequently, female fertility starts to rapidly decline in a woman beyond 37 years of age, as manifest by the success rates of IVF treatment (206) and also by measures of natural fertility (192).…”
Section: Oocyte Qualitymentioning
confidence: 99%
“…It is theoretically possible that CIN may be sufficient to induce tumor formation by directly inactivating the p53 signaling pathway. Experiments in mammalian cells show that the number of chromosome copies proportionately correlates with the level of mRNA in cells (59,60); given that individual human chromosomes encode an estimated thousand genes each, the presence or absence of single chromosomes can have a dramatic effect on whole-cell gene expression. The resulting imbalance has the potential to deregulate cell cycle proteins, tumor suppressors, and oncogenes.…”
Section: Cin In Tumor Initiation and Growthmentioning
confidence: 99%
“…The gene expression study of checkpoint/DNA repair/cell cycle genes at the cleavage stage of Wells et al [2005] showed that embryos with micronuclei, assumed to be caused by lagging or fragmented chromosomes, were associated with elevated levels of the BRCA1 gene. Several studies have shown altered patterns of gene expression in oocytes with the age of women and with aneuploidy [Steuerwald et al, 2007;Fragouli et al, 2010].…”
Section: Possible Genes Involvedmentioning
confidence: 99%